Larger Head Displacement to Optic Flow Presented in the Lower Visual Field. (November 2019) - Fujimoto, Kanon; Ashida, Hiroshi
Optic flow that simulates self-motion often produces postural adjustment. Although literature has suggested that human postural control depends largely on visual inputs from the lower field in the environment, effects of the vertical location of optic flow on postural responses are not well investigated. Here, we examined whether optic flow presented in the lower visual field produces stronger responses than optic flow in the upper visual field. Either expanding or contracting optic flow was presented in upper, lower, or full visual fields through an Oculus Rift head-mounted display. Head displacement and vection strength were measured. Results showed larger head displacement under the optic flow presentation in the full visual field and the lower visual field than the upper visual field, during early period of presentation of the contracting optic flow. Vection was strongest in the full visual field and weakest in the upper visual field. Our findings of lower field superiority in head displacement and vection support the notion that ecologically relevant information has a particularly important role in human postural control and self-motion perception.